Aerodynamic and aeroacoustic experimental investigation of 30P30N high-lift configuration. (March 2018) - Li, Ling; Liu, Peiqing; Guo, Hao; Geng, Xin; Hou, Yujia; Wang, Jinjun
Highlights: Aerodynamic and aeroacoustic experiments of 30P30N multi-element high-lift configuration are conducted in an innovative test section of D5 aeroacoustic wind tunnel at Beihang University, the test section of which is composed of Kevlar and perforated plate. With the measured results of surface pressure distribution, noise source map and far-field noise spectra, this experiment can supplement the database of the 30P30N configuration as the standard model for further study. Abstract: Aerodynamic and aeroacoustic experiments of 30P30N three-element high-lift configuration are conducted in D5 aeroacoustic wind tunnel at Beihang University. The test section is composed of Kevlar and perforated plate which can measure aerodynamic features with less jet shear layer interference and aeroacoustic characteristics with good sound transmission simultaneously. Aiming at the research of high-lift configurations during the aircraft approach and landing, Mach number and angle of attack vary from 0.09 to 0.17 and 3 ° to 8 °, respectively. The measured surface pressure distributions in D5 agree well with the results of JAXA-LWT2 and computational fluid dynamics predictions. Consistent with previous investigations, the far-field noise spectra obtained by 1/2 in. free-field microphones nearly decrease with a slope proportional to f - 2 in a wide frequency range and scale with Ma 4.5 . Moreover, all mid-frequency peaks are observed in the range of 1 < St < 5 with one maximum within St = 1 - 3 . The tonal frequencies and noise spectral shape seem less sensitive to the tested angles of attack, except that the tonal intensity decreases with increasing angles of attack. Noise source maps for 1/3 octave band obtained from data processed by conventional beamforming with the far-field noise spectra indicate that the slat cove and slat-main element region is the main noise source that can radiate narrow-band peaks.